Association between school bags with active commuting to school and musculoskeletal pain - Ávila-García, Manuel; Solís-Urra, Patricio; Huertas-Delgado, Francisco Javier; Tercedor, Pablo; Villa-González, Emilio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aims of this study were; 1- Analyze the mode of commuting of the school children to school, the weight and type of school bags they were carrying and musculoskeletal pain separately by sex. 2- Analyze the association between weights of school bags with mode of commuting to school. A total of 76 children (8.8 ± 0.3 years, 50% children) participated in the study. The Pediatric Pain questionnaire was used to determine the presence or absence of pain. The PACO questionnaire was used to know the mode of commuting to school. The results showed that the active commuting were higher in boys than girls (p =0.042). In addition, there was a significant association between meeting the school bags weight recommended and active commuting from school to home (OR =3.88, p =0.039). Meeting with the weight of the school bags recommended may favor the non-appearance of musculoskeletal pain and active commuting to school.